A carbon nitride-based nickel single-atom photocatalytic material and its preparation method and application
By uniformly dispersing nickel single atoms on the carbon nitride skeleton to form a Ni1-N4/CN structure, the cost and environment of the preparation of olefins in the prior art is solved by uniformly dispersing nickel single atoms on the carbon nitride skeleton to form Ni1-N4/CN structures. The pollution problem has achieved the effect of highly selective transfer of hydrogenated alkyne compounds.
Patent Information
- Application Number
- CN202111681066.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The use of precious metal palladium in the olefin reaction of selective alkyne semihydrogenation results in high costs, environmental pollution and safety risks. The photogenerated carrier recombination rate of a single carbon nitride photocatalytic material is high and the visible light utilization efficiency is low, making it difficult to achieve high Selectively transfer hydrogenated alkyne compounds to olefin compounds.
Develop carbon nitride-based nickel single-atom photocatalytic material, uniformly disperse nickel single atoms on the carbon nitride skeleton through hydrothermal deposition to form a Ni1-N4/CN structure, and catalyzed selective transfer of hydrogenation (deuterated) by alkynes using visible light Synthesis of olefins (deuterated olefins).
It realizes low-cost, high stability and high atomic utilization rate photocatalytic materials, which can transfer hydrogenated alkyne compounds highly selectively under mild conditions, reduce the use of precious metals, avoid heavy metal pollution and hydrogen safety hazards, and improve catalytic activity. and efficiency.
Smart Images

Figure CN116408123B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic organic synthesis materials and nanomaterial synthesis, and relates to a carbon nitride-based nickel single-atom photocatalytic material, a preparation method and application thereof, and specifically relates to a nano photocatalytic material in which metal is dispersed on a carbon nitride skeleton at the single-atom level, a preparation method thereof, and an application thereof in the synthesis of olefins (deuterated olefins) by highly selective transfer hydrogenation (deuteration) of alkynes. Background Art
[0002] Olefin compounds are very important building blocks in the synthesis of various natural products, drug molecules and polymers. Lindler catalyst (which is composed of precious metal palladium supported on a calcium carbonate carrier) is often used in industry to achieve selective semi-hydrogenation of alkynes to produce olefins, with lead acetate and quinoline as deactivators and hydrogen as a hydrogen source.
[0003] However, in the existing selective semi-hydrogenation of alkynes to prepare olefins, the use of precious metal palladium makes the olefin production cost too high, and the use of lead acetate will inevitably cause heavy metal pollution to the environment. At the same time, hydrogen is an explosive substance, which will bring serious safety hazards to industrial production. Therefore, people are in urgent need of developing new catalysts that can avoid the use of precious metal palladium, toxic metal lead and explosive hydrogen, and can achieve selective transfer hydrogenation of alkyne compounds to olefin compounds under mild conditions.
[0004] Carbon nitride (CN) has become a photocatalytic material with great application prospects due to its unique visible light responsiveness, simple preparation, low cost, and good photostability. However, single carbon nitride photocatalytic materials have the disadvantages of high probability of recombination of photogenerated carriers and low visible light utilization efficiency. Therefore, it is still necessary to induce the rapid separation and migration of photogenerated electrons by photodeposition of precious metals such as Pd, Pt, and Au as co-catalysts to increase the active sites of photocatalytic reactions. However, precious metal co-catalysts are usually loaded on the surface of carbon nitride in the form of nanoparticles, and the atomic dispersion is poor, resulting in low electron transfer efficiency between carbon nitride carriers and metal nanoparticles, making it difficult to give full play to the co-catalytic ability of each precious metal atom. Therefore, it is urgent to develop a low-cost, high-atomic utilization and high-stability photocatalytic material to achieve a new method for highly selective transfer of hydrogenated alkyne compounds to olefin compounds. Summary of the invention
[0005] In view of the above defects in the prior art, the purpose of the present invention is to provide a carbon nitride-based nickel single-atom photocatalytic material and a preparation method thereof and an application thereof in the selective transfer hydrogenation (deuteration) of alkynes to synthesize olefins (deuterated olefins). The photocatalytic material of the present invention has low preparation cost, high stability, high atomic utilization rate, can be mass-produced, and can synthesize olefins (deuterated olefins) compounds by highly selective transfer hydrogenation (deuteration) of alkyne compounds using visible light under mild conditions.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] The invention provides a carbon nitride-based nickel single-atom material, which comprises carbon nitride and nickel metal loaded in a carbon nitride skeleton in a single-atom-level dispersed form.
[0008] According to an embodiment of the present invention, the carbon nitride-based nickel single atom material is represented by Ni1-N4 / CN, Ni1-N4 represents nickel single atoms and their coordination structures, and CN represents carbon nitride.
[0009] According to an embodiment of the present invention, the carbon nitride-based nickel single-atom material is a nanomaterial.
[0010] According to an embodiment of the present invention, in the carbon nitride-based nickel single-atom material, the mass ratio of nickel single atom (Ni) to CN is 1:(67-500), preferably 1:(200-300), and exemplarily 1:500, 1:400, 1:300, 1:200, 1:100, and 1:67.
[0011] According to an embodiment of the present invention, in Ni1-N4 / CN, one nickel atom coordinates with four nitrogen atoms in the carbon nitride skeleton, thereby being anchored in the carbon nitride skeleton to form a Ni1-N4 single active site.
[0012] According to an embodiment of the present invention, in Ni1-N4 / CN, the particle size of a single nickel atom may be 0.1 to 2 nm, preferably 0.1 to 0.2 nm, and nickel is supported in the carbon nitride skeleton in a dispersed form at the single atomic level.
[0013] According to an embodiment of the present invention, the Ni1-N4 / CN has substantially Figure 1 The X-ray powder diffraction spectrum is shown.
[0014] According to an embodiment of the present invention, the Ni1-N4 / CN has substantially Figure 3 The shape shown.
[0015] According to an embodiment of the present invention, in the carbon nitride-based nickel single-atom material, the maximum visible light absorption peak of the Ni1-N4 / CN is between 385 and 395 nm, preferably at 390 nm. Preferably, the Ni1-N4 / CN has substantially Figure 6 UV-visible absorption spectrum shown.
[0016] The present invention also provides a method for preparing the above-mentioned carbon nitride-based nickel single-atom material, comprising using a compound containing a nickel element and carbon nitride as raw materials, and preparing the carbon nitride-based nickel single-atom material by hydrothermal deposition under the action of an organic amine.
[0017] According to an embodiment of the present invention, the carbon nitride can be prepared by sintering a carbon nitride precursor. For example, the carbon nitride precursor can be selected from small molecules containing both carbon and nitrogen.
[0018] Preferably, the carbon nitride precursor is selected from one, two or more of dicyandiamide, melamine, urea and benzoguanamine, preferably urea.
[0019] Preferably, the sintering temperature is 500-600°C, exemplarily 500°C, 550°C or 600°C.
[0020] Preferably, the sintering time is 2 to 16 hours, exemplified by 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, and 16 hours.
[0021] Preferably, the heating rate of the sintering is 2-10°C / min, exemplified by 2°C / min, 5°C / min, and 10°C / min.
[0022] Different precursor molecules have different chemical properties, so the crystallinity of carbon nitride obtained by high-temperature calcination is also different, which will also affect the kinetic behavior of photogenerated carriers of the catalyst, and further affect the photocatalytic performance of carbon nitride-based nickel single-atom materials. The carbon nitride used in the present invention has high crystallinity.
[0023] Furthermore, after the sintering is completed, the sintered product is ground.
[0024] Preferably, the preparation of carbon nitride further comprises ultrasonically treating the powder obtained after grinding.
[0025] For example, the ultrasonic treatment is carried out in an organic solvent. For another example, the organic solvent can be selected from at least one of acetone, N,N-dimethylformamide, dichloromethane, chloroform, methanol, ethanol, N,N-dimethylacetamide, and acetonitrile. Further, the ultrasonic treatment time is 10 to 60 minutes, exemplified by 10 minutes, 20 minutes, 40 minutes, and 60 minutes.
[0026] Preferably, the preparation of carbon nitride further comprises liquid phase exfoliation of the product after ultrasonic treatment to obtain carbon nitride nanosheets. For example, the liquid phase exfoliation time is 10 to 60 minutes, exemplified by 10 minutes, 20 minutes, 40 minutes, and 60 minutes.
[0027] According to an embodiment of the present invention, the compound containing nickel element can be provided by organic or inorganic matter containing nickel element; preferably provided by inorganic matter containing nickel element. For example, the compound containing nickel element can be selected from one, two or more of the following compounds: chloride, nitrate, acetate, sulfate and carbonate containing nickel element; preferably chloride containing nickel element.
[0028] According to an exemplary embodiment of the present invention, the compound containing nickel element is selected from one, two or more of nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel perchlorate and hydrates thereof (such as nickel nitrate hexahydrate, nickel chloride hexahydrate, nickel sulfate hexahydrate, nickel acetate tetrahydrate, nickel perchlorate hexahydrate), preferably nickel chloride hexahydrate.
[0029] Preferably, the mass ratio of the carbon nitride to the compound containing nickel element is (400:1) to (10:1), and exemplary ratios are 400:1, 300:1, 200:1, 100:1, 54:1, 25:1, and 12:1.
[0030] When the mass ratio of carbon nitride to the compound containing nickel is too high, the metal loading will drop sharply, resulting in a reduction in catalytic active sites; while if the raw material ratio is too small (i.e., the amount of the compound containing nickel is too high), nickel metal will form clusters or nanoparticles on the surface of carbon nitride, thereby reducing the dispersion of nickel metal atoms and further reducing the catalytic performance.
[0031] According to an embodiment of the present invention, the organic amine can be selected from at least one of triethanolamine, triethylamine, n-propylamine and N,N-diisopropylethylamine. The addition of the organic amine can promote the slow dissolution of the compound containing the nickel element, so that the nickel metal is evenly dispersed and coordinated to the carbon nitride skeleton at the atomic level, thereby fully exposing the active sites on the surface of the carbon nitride-based nickel single-atom material.
[0032] According to an embodiment of the present invention, the mass ratio of carbon nitride to organic amine is (4:1) to (1:2), exemplified by 4:1, 3:1, 2:1, 1:1, and 1:2.
[0033] According to an embodiment of the present invention, the method for preparing the carbon nitride-based nickel single-atom material further comprises stirring the reaction mixture. The present invention does not particularly require the stirring time, and the nickel metal salt and the carbon nitride suspension are mixed. For example, the reaction mixture is stirred overnight. Stirring is conducive to making the dissolved nickel metal salt more evenly coordinated in the carbon nitride skeleton.
[0034] According to an embodiment of the present invention, the temperature of the hydrothermal deposition is 40 to 160°C, preferably 60 to 140°C, and exemplified by 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, and 160°C; further, the time of the hydrothermal deposition is 4 to 32h, preferably 8 to 24h, and exemplified by 4h, 8h, 12h, 16h, 24h, and 32h.
[0035] In the present invention, the coordination effect between the pre-coordinated nickel metal single atom and the carbon nitride support can be further enhanced by hydrothermal deposition, thereby maximally ensuring that the nickel metal is dispersed in the carbon nitride skeleton at the single-atom level. In addition, the hydrothermal deposition conditions are mild and effective, which greatly avoids the high energy consumption, poor reproducibility and safety hazards of high-temperature synthesis operations caused by the traditional high-temperature calcination method for synthesizing single-atom catalysts.
[0036] According to an embodiment of the present invention, the preparation method further comprises a step of performing solid-liquid separation on the reaction system after the reaction is completed. For example, the solid-liquid separation can be performed by means known in the art, such as centrifugation and filtration.
[0037] According to an embodiment of the present invention, the preparation method further comprises washing the reaction product obtained by solid-liquid separation. Preferably, the solvent used for washing can be an organic solvent. For example, chloroform, methanol, or acetonitrile is used for washing.
[0038] According to an embodiment of the present invention, the preparation method further comprises drying the washed reaction product. For example, the drying method may be at least one of freeze drying, vacuum drying, and constant temperature evaporation, preferably constant temperature evaporation. Further, the temperature of the constant temperature evaporation method may be 40 to 60°C, exemplified by 40°C, 50°C, and 60°C. Constant temperature evaporation can cause the solvent to evaporate slowly and evenly, so as to facilitate the uniform distribution of metal atoms in the carbon nitride molecular skeleton.
[0039] According to an embodiment of the present invention, the method for preparing the carbon nitride-based nickel single-atom material comprises the following steps:
[0040] Step (1): calcining a carbon nitride precursor at 500-600° C. for 2-16 hours to obtain carbon nitride;
[0041] Step (2): grinding the carbon nitride obtained in step (1) to obtain a powdered solid, dispersing it in an organic solvent, performing ultrasonic treatment, and then continuing liquid phase exfoliation to obtain a dispersed carbon nitride nanosheet suspension; then mixing the suspension with a compound containing nickel and an organic amine, and stirring;
[0042] Step (3): subjecting the mixed solution obtained in step (2) to hydrothermal deposition to obtain the carbon nitride-based nickel single-atom material.
[0043] The present invention also provides the use of the above carbon nitride-based nickel single atom material as a photocatalytic material. Preferably, the use of the above carbon nitride-based nickel single atom material in the preparation of olefin compounds by catalytic selective transfer hydrogenation of alkyne compounds; for example, the olefin compounds are olefin compounds or deuterated olefin compounds.
[0044] Preferably, the invention is used in the catalytic selective transfer hydrogenation of alkyne compounds to prepare olefin compounds or deuterated olefin compounds.
[0045] The present invention also provides a method for preparing olefin compounds by photocatalysis, the method comprising: reacting an alkyne compound with light under the action of the above-mentioned carbon nitride-based nickel single-atom material to prepare the olefin compound.
[0046] According to an embodiment of the present invention, the olefin compound is an olefin compound or a deuterated olefin compound.
[0047] According to an embodiment of the present invention, the alkyne compound is selected from one, two or more of an aromatic compound containing an alkynyl functional group and an aliphatic compound containing an alkynyl functional group.
[0048] Preferably, except for the reaction site containing the alkynyl functional group, other sites of the aromatic compound containing the alkynyl functional group and the aliphatic compound containing the alkynyl functional group are unsubstituted or substituted by inert groups and / or active groups; for example, the inert group can be selected from fluorine, chlorine, bromine, trifluoromethyl; for example, the active group can be selected from phenyl, methoxy, tert-butyl, and n-pentyl. For example, the alkyne compound can be selected from aromatic compounds containing alkynyl functional groups substituted by 1 bromine atom or 1 chlorine atom, such as 1-bromo-4-ethynylbenzene, 1-chloro-4-ethynylbenzene, or aromatic compounds containing alkynyl functional groups substituted by 1 tert-butyl group or 1 alkoxy group, such as 4-tert-butylphenylacetylene, 4-ethynylanisole.
[0049] According to an exemplary embodiment of the present invention, the alkyne compound includes but is not limited to one, two or more of the following compounds: phenylacetylene, 1-bromo-4-(phenylethynyl)benzene, 1-ethynyl-2-fluorobenzene, 2-ethynylnaphthalene, cyclohexylacetylene, 4-fluorophenylacetylene, 4-chlorophenylacetylene, (4-bromophenyl)acetylene, 1-chloro-4-ethynylbenzene, 1-bromo-4-ethynylbenzene and 4-ethynyltoluene.
[0050] According to an embodiment of the present invention, the reaction is carried out in a solvent. Preferably, the solvent can be selected from at least one of an alcohol solvent, an aromatic hydrocarbon solvent, a nitrile solvent, a ketone solvent, a hydrocarbon solvent, an ether solvent, and a corresponding deuterated solvent, deuterated water, etc.
[0051] Preferably, the alcohol solvent can be selected from at least one of methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, tert-butanol, pentanol, decanol, n-dodecyl alcohol, cyclopentanol, cyclohexanol, benzyl alcohol, phenylethyl alcohol, and trimethylpentanediol, for example, methanol.
[0052] Preferably, the aromatic hydrocarbon solvent may be selected from at least one of toluene, chlorobenzene and bromobenzene.
[0053] Preferably, the nitrile solvent may be selected from acetonitrile.
[0054] Preferably, the ketone solvent may be selected from acetone.
[0055] Preferably, the hydrocarbon solvent may be selected from n-hexane.
[0056] Preferably, the ether solvent can be selected from tetrahydrofuran or diethyl ether.
[0057] According to an embodiment of the present invention, the method for preparing olefin compounds by photocatalysis further comprises adding a sacrificial agent to the reaction system. Preferably, the sacrificial agent may be an organic amine or an alcohol.
[0058] According to an embodiment of the present invention, the organic amine is an aliphatic organic amine, for example, at least one of triethylamine, triethanolamine, n-propylamine and N,N-diisopropylethylamine, preferably triethylamine.
[0059] According to an embodiment of the present invention, the mass ratio of the carbon nitride-based nickel single-atom material to the alkyne compound can be 100:1 to 1:100, preferably 5:1 to 1:100, and more preferably 1:1 to 1:50. Exemplary ratios are 100:1, 50:1, 20:1, 10:1, 5:1, 1:1, 1:5, 1:10, 1:20, 1:50, and 1:100.
[0060] According to an embodiment of the present invention, the reaction time may be more than 1 h, preferably 1 to 40 h, more preferably 3 to 25 h, exemplified by 1 h, 3 h, 5 h, 8 h, 10 h, 12 h, 14 h, 16 h, 24 h, 25 h, 30 h, and 40 h.
[0061] According to an embodiment of the present invention, the reaction temperature may be 0 to 100°C, such as 10 to 60°C, and further such as 30 to 90°C.
[0062] According to an embodiment of the present invention, the reaction is carried out under sealed conditions.
[0063] According to an embodiment of the present invention, the reaction is carried out in an oxygen-free environment, for example, in an inert gas (such as argon).
[0064] According to an embodiment of the present invention, the light irradiation reaction is carried out under stirring conditions.
[0065] According to an embodiment of the present invention, the light irradiation is visible light irradiation.
[0066] According to an embodiment of the present invention, the method for preparing olefin compounds by photocatalysis comprises the following steps:
[0067] Under the protection of inert gas, an alkyne compound, a sacrificial agent and a catalyst are added into a solvent, mixed and stirred, and reacted under visible light irradiation to obtain an olefin compound.
[0068] According to an embodiment of the present invention, the method for preparing deuterated olefin compounds by photocatalysis comprises the following steps:
[0069] Under the protection of inert gas, an alkyne compound, a sacrificial agent and a catalyst are added into a deuterated solvent, mixed and stirred, and irradiated with visible light for reaction to obtain a deuterated olefin compound.
[0070] Beneficial effects of the present invention:
[0071] (1) The present invention can obtain highly crystalline carbon nitride molecules by controlling the temperature and calcination rate of the calcined carbon nitride precursor within an appropriate range to reduce defect sites in the carbon nitride skeleton, thereby reducing the recombination of photogenerated carriers. At the same time, the present invention adopts a post-synthesis method, that is, it breaks through the limitations of the previous high-temperature calcination method and adopts a hydrothermal deposition method with a milder temperature, which can more easily synthesize single-atom dispersed carbon nitride-based photocatalytic materials at a lower temperature. Thereby overcoming the problems of high energy consumption, poor reproducibility, and poor crystallinity of carbon nitride in the existing high-temperature calcination of carbon nitride precursors and metal salt molecular complexes to prepare single atoms. The method of the present invention can obtain carbon nitride-based nickel single-atom materials with different loading amounts by adjusting the mass ratio of carbon nitride to the compound containing nickel elements.
[0072] (2) The present invention prepares a novel photocatalytic material of carbon nitride-based single-atom-loaded noble metal by mixing noble metal ions with carbon nitride, adding organic amine to assist the slow dissolution of the noble metal ions, and then using a solvothermal method. In the photocatalytic material of the present invention, nickel metal is uniformly distributed in the carbon nitride skeleton at the single-atom level to form highly dispersed active sites to improve its photocatalytic activity.
[0073] (3) In the carbon nitride-based nickel single atom material of the present invention, the nickel single atom coordinates with the nitrogen atoms on the surrounding carbon nitride to form a stable Ni1-N4 coordination structure, which is anchored in the carbon nitride skeleton. Before the light reaction, the metal nickel single atom is stably anchored in the carbon nitride skeleton in a positive divalent state; during the photocatalytic reaction, the positive divalent nickel single atom is reduced to a low-valent state by photogenerated electrons to form a photocatalytic material with a single nickel active site, thereby significantly improving the utilization efficiency of metal atoms, effectively inhibiting the recombination of photogenerated carriers, increasing the reaction active sites on the carbon nitride surface, and further significantly improving the catalytic activity.
[0074] (4) The present invention selects a suitable polar solvent, which is conducive to the slow and uniform deposition of metal salts into the carbon nitride molecular skeleton, so as to help fully expose the surface catalytic reaction active sites. In addition, ultrasonic dispersion and liquid phase exfoliation can cause the carbon nitride multilayer material to be exfoliated into a few layers through the action of force, thereby increasing the specific surface area of the carbon nitride to expose more coordination sites on the surface of the carbon nitride skeleton, thereby enhancing the coordination effect between the metal nickel single atom and the carbon nitride carrier, thereby enhancing the transfer rate of the carbon nitride photogenerated electrons to the single atom nickel, and thus improving the photocatalytic performance.
[0075] (5) The preparation method of the present invention has mild conditions and low raw material cost, and has broad application prospects in the fields of photocatalytic organic synthesis, energy conversion and environmental remediation. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 X-ray powder diffraction spectra of carbon nitride (represented by CN in the figure) and carbon nitride-based nickel single-atom material (represented by Ni1-N4 / CN in the figure) (Ni1-N4 / CN-1.85 in the figure represents the material obtained by compounding 100 mg carbon nitride and 1.85 mg NiCl2·6H2O).
[0077] Figure 2 Fourier infrared spectra of carbon nitride (represented by CN in the figure) and carbon nitride-based nickel single-atom material (represented by Ni1-N4 / CN-1.85 in the figure) (Ni1-N4 / CN-1.85 in the figure represents the material obtained by combining 100 mg carbon nitride and 1.85 mg NiCl2·6H2O).
[0078] Figure 3This is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image of carbon nitride-based nickel single-atom photocatalytic material.
[0079] Figure 4 High-resolution transmission electron microscopy (HRTEM) images and element distribution spectra of carbon nitride-based nickel single-atom materials.
[0080] Figure 5 This is the X-ray absorption near-edge structure (XANES) spectrum of carbon nitride-based nickel single-atom material (in the figure, Nifoil represents metal nickel foil, and Ni1-N4 / CN-1.85 represents the photocatalytic material obtained by combining 100 mg carbon nitride and 1.85 mg NiCl2.6H2O).
[0081] Figure 6 It is the UV-visible absorption spectra of carbon nitride (represented by CN in the figure) and carbon nitride-based nickel single-atom material (represented by Ni1-N4 / CN-1.85 in the figure), (Ni1-N4 / CN-1.85 in the figure represents the photocatalytic material obtained by compounding 100 mg carbon nitride and 1.85 mg NiCl2·6H2O).
[0082] Figure 7 It is the photoluminescence spectrum of carbon nitride (represented by CN in the figure) and carbon nitride-based nickel single atom material (represented by Ni1-N4 / CN-1.85 in the figure, where Ni1-N4 / CN-1.85 represents the photocatalytic material obtained by compounding 100 mg carbon nitride and 1.85 mg NiCl2·6H2O).
[0083] Figure 8 Gas chromatography (GC) detection chart of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using methanol as the hydrogen source on carbon nitride-based nickel single atom material.
[0084] Fig. 9 This is the mass spectrometry (MS) detection diagram of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using methanol as the hydrogen source on carbon nitride-based nickel single atom material.
[0085] Fig.10 Gas chromatography (GC) detection chart of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using carbon nitride-based nickel single atom material with water as the hydrogen source.
[0086] Fig.11 This is the mass spectrometry (MS) detection diagram of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using carbon nitride-based nickel single atom material with water as the hydrogen source.
[0087] Fig.12Gas chromatography (GC) detection chart of the photocatalytic selective transfer of deuterated 2-acetylenonaphthalene to prepare deuterated 2-vinylnaphthalene using deuterated water as a deuterium source on carbon nitride-based nickel single-atom material.
[0088] Fig.13 Mass spectrometry (MS) detection diagram of the photocatalytic selective transfer of deuterated 2-acetylenonaphthalene to prepare deuterated 2-vinylnaphthalene using deuterated water as a deuterium source on carbon nitride-based nickel single atom material.
[0089] Fig.14 The nuclear magnetic resonance hydrogen spectrum detection image of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to 2-vinylnaphthalene using water as a hydrogen source on a single-atom nickel carbon nitride material ( 1 1H NMR).
[0090] Fig.15 This is the nuclear magnetic resonance hydrogen spectrum detection diagram (1H NMR) of the photocatalytic selective transfer of deuterated 2-acetylenonaphthalene to prepare deuterated 2-vinylnaphthalene using deuterated water as the deuterium source on carbon nitride-based nickel single atom material. DETAILED DESCRIPTION
[0091] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0092] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0093] In the following examples of the present invention, an Agilent 7890 gas chromatograph equipped with a flame ionization detector (GC-FID) equipped with a DB-WAX chromatographic column (30m×530μm×1μm) was used to quantitatively determine the yield of the reaction product using a calibration curve of a standard substance of styrene.
[0094] The X-ray absorption near-edge structure (XANES) spectrum of carbon nitride-based nickel single atom material was measured at the 1W2B beamline of the Beijing Synchrotron Radiation Facility (BSRF).
[0095] Example 1
[0096] 10g of urea was transferred to a ceramic crucible and calcined at 550℃ for 8 hours to obtain a carbon nitride bulk material. After that, the carbon nitride bulk material was transferred to an agate mortar and ground to obtain carbon nitride powder, and then 600mg of carbon nitride powder was dispersed in 60mL of acetonitrile, ultrasonicated for 30min, and then liquid phase exfoliation was continued for 30min to obtain a dispersed carbon nitride nanosheet suspension. After that, it was transferred to six 20mL sample bottles in six equal parts, and 1.85mg NiCl2·6H2O and 80μL triethylamine were added to each sample bottle, and then stirred at room temperature overnight. Then, it was hydrothermally deposited at 80℃ for 16h and naturally cooled to room temperature. Finally, the obtained reaction solution was washed twice with chloroform, methanol, and acetonitrile respectively, and then vacuum dried to obtain a carbon nitride-based single-atom nickel photocatalytic material with a mass content of 0.32% of nickel single atoms, recorded as Ni1-N4 / CN-1.85.
[0097] Figure 1 The X-ray powder diffraction spectra of the carbon nitride powder (represented by CN in the figure) and the carbon nitride-based nickel single-atom photocatalytic material (represented by Ni1-N4 / CN-1.85 in the figure) prepared in this embodiment (Ni1-N4 / CN-1.85 in the figure represents the material obtained by compounding 100 mg of carbon nitride with 1.85 mg of NiCl2·6H2O). The comparison of the results of the two samples in the figure shows that the X-ray powder diffraction spectra of the carbon nitride-based nickel single-atom photocatalytic material and the carbon nitride powder are basically consistent. This shows that the present invention does not change the crystallinity of the carbon nitride powder by using mild hydrothermal deposition to load nickel single atoms, and thus does not change the intrinsic photodynamic behavior of the carbon nitride powder.
[0098] Figure 2 The Fourier infrared spectra of the carbon nitride powder (represented by CN in the figure) and the carbon nitride-based nickel single-atom photocatalytic material (represented by Ni1-N4 / CN-1.85 in the figure) prepared in this embodiment (Ni1-N4 / CN-1.85 in the figure represents the material obtained by compounding 100 mg of carbon nitride with 1.85 mg of NiCl2.6H2O). The results in the figure show that the Fourier infrared spectrum of the carbon nitride-based nickel single-atom photocatalytic material is basically consistent with the Fourier infrared spectrum of the carbon nitride powder. This shows that the present invention does not change the surface functional groups of the carbon nitride powder by using mild hydrothermal deposition to load nickel single atoms, thereby retaining the intrinsic structure of the carbon nitride powder.
[0099] Figure 3 This is a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) photo of the carbon nitride-based nickel single-atom photocatalytic material prepared in this embodiment. The dispersed bright white dots in the figure are shown as metal nickel dispersed at the single-atom level, which shows that the present invention successfully prepares the carbon nitride-based nickel single-atom photocatalytic material by adopting a mild hydrothermal deposition method.
[0100] Figure 4 The high-resolution transmission electron microscope (HRTEM) photo and element distribution spectrum of the carbon nitride-based nickel single-atom photocatalytic material prepared in this embodiment. The high-resolution transmission electron microscope image shows that the carbon nitride-based nickel single-atom photocatalytic material exists in the form of stacked nanosheets; the element distribution spectrum shows that in the carbon nitride-based nickel single-atom photocatalytic material, carbon and nitrogen elements are evenly distributed, and nickel elements are distributed among carbon and nitrogen elements, which shows that the present invention successfully loads nickel single atoms on the carbon nitride substrate by adopting a mild hydrothermal deposition method.
[0101] Figure 5 The extended X-ray absorption fine structure (EXAFS) spectrum of the carbon nitride-based nickel single-atom photocatalytic material prepared in this embodiment (Ni foil in the figure represents metal nickel foil, and Ni1-N4 / CN-1.85 represents the photocatalytic material obtained by compounding 100 mg carbon nitride with 1.85 mg NiCl2·6H2O). The results in the figure show that compared with the metal nickel foil, the X-ray front absorption position of the carbon nitride-based nickel single-atom photocatalytic material moves to the high-energy region, indicating that nickel is loaded in the carbon nitride skeleton in an oxidized state, and further indicating that there are no metallic nickel nanoparticles in the carbon nitride skeleton, thereby proving that the method of the present invention successfully prepares a carbon nitride-based nickel single-atom photocatalytic material dispersed at the single-atom level.
[0102] Figure 6 The ultraviolet-visible absorption spectra of the carbon nitride powder (represented by CN in the figure) and the carbon nitride-based nickel single-atom photocatalytic material (represented by Ni1-N4 / CN-1.85 in the figure) prepared in this embodiment (Ni1-N4 / CN-1.85 in the figure represents the photocatalytic material obtained by compounding 100 mg of carbon nitride with 1.85 mg of NiCl2·6H2O). The results in the figure show that compared with the carbon nitride powder, the carbon nitride-based nickel single-atom photocatalytic material shows a stronger light absorption intensity in the 300-500nm wavelength region, which further indicates that the carbon nitride-based nickel single-atom photocatalytic material has a stronger light absorption performance than the carbon nitride powder, which is beneficial to the photocatalytic reaction.
[0103] Figure 7The photoluminescence spectra of the carbon nitride powder (represented by CN in the figure) and the carbon nitride-based nickel single-atom photocatalytic material (represented by Ni1-N4 / CN-1.85 in the figure) prepared in this embodiment (excitation wavelength is 350nm, and Ni1-N4 / CN-1.85 in the figure represents the photocatalytic material obtained by compounding 100mg carbon nitride with 1.85mg NiCl2·6H2O). The results in the figure show that compared with the carbon nitride powder, the carbon nitride-based nickel single-atom photocatalytic material shows a lower fluorescence intensity, indicating that it has a lower recombination rate of photogenerated electrons and photogenerated holes, and further indicates that it has a faster photogenerated carrier migration speed, thereby indicating that the carbon nitride-based nickel single-atom photocatalytic material has better photocatalytic performance.
[0104] Comparative Example 1
[0105] 10g of urea was transferred to a ceramic crucible and calcined at 550°C for 8 hours to obtain a carbon nitride bulk material. Afterwards, the carbon nitride bulk material was transferred to an agate mortar and ground to obtain carbon nitride powder. Then 100mg of carbon nitride powder was dispersed in 20mL of water, ultrasonicated for 30min, and then liquid phase exfoliation was continued for 30min to obtain a dispersed carbon nitride nanosheet suspension. Afterwards, 765μL of 10 -2 M Ni(NO3)2·6H2O aqueous solution was slowly added dropwise to the above suspension and stirred at room temperature for 30 min. Then, 5 mL NaBH4 aqueous solution (5.8 mg NaBH4) was slowly added dropwise and stirred at room temperature for 30 min. Finally, the obtained reaction solution was washed twice with water and vacuum dried to obtain a carbon nitride-based nickel nanoparticle comparison sample with a mass content of 0.32% of nickel nanoparticles, denoted as Ni / CN.
[0106] Application Example 1
[0107] 10 mg of the Ni1-N4 / CN-1.85 sample obtained in Example 1 was added to 10 mL of methanol solvent, and then 0.1 mmol of phenylacetylene and 0.5 mmol of triethylamine were added and mixed thoroughly, and then the photoreactor was sealed, and high-purity argon was introduced for 30 min to remove oxygen in the photochemical reactor. After deoxygenation, stirring was continued, and the reaction was stopped after irradiation with a 420 nm LED light source for 7 h. The reaction product was mainly styrene, and the yield of styrene detected by gas chromatography was 91%.
[0108] Comparative application example 1
[0109] 10 mg of the Ni / CN sample prepared in Comparative Example 1 was added to 10 mL of methanol solvent, and then 0.1 mmol of phenylacetylene and 0.5 mmol of triethylamine were added and mixed thoroughly, and then the photoreactor was sealed, and high-purity argon was introduced for 30 min to remove oxygen in the photochemical reactor. After deoxygenation, stirring was continued, and the reaction was stopped after irradiation with a 420 nm LED light source for 7 h. The reaction product was mainly styrene, and the yield of styrene was 32% as determined by gas chromatography.
[0110] Example 2
[0111] 10g of urea was transferred to a ceramic crucible and calcined at 550℃ for 8 hours to obtain a carbon nitride bulk material. After that, the carbon nitride bulk material was transferred to an agate mortar and ground to obtain fine carbon nitride powder, and then 600mg of carbon nitride powder was dispersed in 60mL of acetonitrile, ultrasonicated for 30min, and then liquid phase exfoliation was continued for 30min to obtain a dispersed carbon nitride nanosheet suspension. After that, it was transferred to six 20mL sample bottles in six equal parts, and 4.05mgNiCl2.6H2O and 80μL triethylamine were added to each sample bottle, and then stirred at room temperature overnight. Then, it was hydrothermally deposited at 80℃ for 16h and naturally cooled to room temperature. Finally, the obtained reaction solution was washed twice with chloroform, methanol, and acetonitrile, respectively, and vacuum dried to obtain a carbon nitride-based single-atom nickel photocatalytic material with a mass content of 1% of nickel single atoms, recorded as Ni1-N4 / CN-4.05.
[0112] Application Example 2
[0113] 10 mg of the Ni1-N4 / CN-4.05 sample prepared in Example 2 was added to 10 mL of methanol solvent, and then 0.1 mmol of phenylacetylene and 0.5 mmol of triethylamine were added and mixed thoroughly, and then the photoreactor was sealed, and high-purity argon was introduced for 30 min to remove oxygen in the photochemical reactor. After deoxygenation, stirring was continued, and the reaction was stopped after irradiation with a 420 nm LED light source for 7 h. The reaction product was mainly styrene, and the gas chromatographic yield was 78%.
[0114] Example 3
[0115] 10g of urea was transferred to a ceramic crucible and calcined at 550℃ for 8 hours to obtain a carbon nitride bulk material. After that, the carbon nitride bulk material was transferred to an agate mortar and ground to obtain fine carbon nitride powder, and then 600mg of carbon nitride powder was dispersed in 60mL of acetonitrile, ultrasonicated for 30min, and then liquid phase exfoliation was continued for 30min to obtain a dispersed carbon nitride nanosheet suspension. After that, it was transferred to six 20mL sample bottles in six equal parts, and 8.10mgNiCl2·6H2O and 80μL triethylamine were added to each sample bottle, and then stirred at room temperature overnight. Then, it was hydrothermally deposited at 80℃ for 16h and naturally cooled to room temperature. Finally, the obtained reaction solution was washed twice with chloroform, methanol, and acetonitrile respectively, and then vacuum dried to obtain a carbon nitride-based single-atom nickel photocatalytic material, recorded as Ni1-N4 / CN-8.10.
[0116] Application Example 3
[0117] 10mg Ni1-N4 / CN-8.10 sample was added to 10mL methanol solvent, and then 0.1mmol phenylacetylene and 0.5mmol triethylamine were added and mixed well, then the photoreactor was sealed, and high-purity argon was introduced for 30min to remove oxygen in the photochemical reactor. After deoxygenation, stirring was continued, and the reaction was stopped after irradiation with a 420nm LED light source for 7h. The reaction product was mainly styrene, and the yield of styrene was 82% as determined by gas chromatography.
[0118] Application Example 4
[0119] The Ni1-N4 / CN-1.85 sample that 10mg embodiment 1 is made is added in the 10mL methanol solvent, after adding 0.1mmol 2-ethynylnaphthalene and 0.5mmol triethylamine and fully mixing, then with the photoreactor sealing, feed high-purity argon 30min to get rid of the oxygen in the photochemical reactor, after deoxygenation finishes, continue to stir, and adopt the stopped reaction after the 420nm LED light source irradiation 10h.Reaction product is mainly 2-vinylnaphthalene, and isolated yield is 85% (isolated yield is separated by column chromatography, and rotary evaporation obtains the 2-vinylnaphthalene product, and the quality calculation that obtains the 2-vinylnaphthalene product by weighing then obtains).
[0120] Figure 8 Gas chromatography (GC) detection chart of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to 2-vinylnaphthalene using methanol as the hydrogen source over carbon nitride-based nickel single atom photocatalytic material (Ni1-N4 / CN-1.85).
[0121] Fig. 9Mass spectrometry (MS) detection diagram of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using methanol as the hydrogen source using carbon nitride-based nickel single atom photocatalytic material (Ni1-N4 / CN-1.85).
[0122] Fig.10 Photocatalytic selective transfer hydrogenation of 2-ethynylnaphthalene to 2-vinylnaphthalene using methanol as hydrogen source on a carbon nitride-based nickel single atom photocatalytic material (Ni1-N4 / CN-1.85) was recorded on a 400 MHz Bruker Avance NMR spectrometer. 1 H NMR spectrum). 1 H NMR (400MHz, Methanol-d4) δ7.89-7.31 (m, 7H), 6.89 (dd, J=17.6, 10.9Hz, 1H), 5.88 (d, J=17.6Hz, 1H), 5.30 (d, J=10.9Hz, 1H).
[0123] The above characterizations prove that 2-vinylnaphthalene was successfully prepared.
[0124] Application Example 5
[0125] The Ni1-N4 / CN-1.85 sample that 20mg embodiment 1 is made is added in the mixed solvent of 10mL acetonitrile and water (volume ratio is 7: 3), after adding 0.1mmol 2-ethynylnaphthalene and 0.5mmol triethylamine and fully mixing, then with the photoreactor sealing, feed high-purity argon 30min to get rid of the oxygen in the photochemical reactor, after deoxygenation finishes, continue to stir, and adopt 420nm LED light source to irradiate 3h after stopped reaction.Reaction product is mainly 2-vinylnaphthalene, and the productive rate of 2-vinylnaphthalene through gas chromatographic detection is 87%.
[0126] Fig.11 Gas chromatography (GC) detection chart of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using carbon nitride-based nickel single-atom photocatalytic material (Ni1-N4 / CN-1.85) with water as the hydrogen source.
[0127] Fig.12 Mass spectrometry (MS) detection diagram of the photocatalytic selective transfer hydrogenation of 2-acetylenonaphthalene to prepare 2-vinylnaphthalene using water as the hydrogen source over carbon nitride-based nickel single-atom photocatalytic material (Ni1-N4 / CN-1.85).
[0128] The above characterizations prove that 2-vinylnaphthalene was successfully prepared.
[0129] Application Example 6
[0130] The Ni1-N4 / CN-1.85 sample that 20mg embodiment 1 is made is added in the mixed solvent of 10mL acetonitrile and deuterated water (volume ratio is 7: 3), after adding 0.1mmol 2-ethynylnaphthalene and 0.5mmol triethylamine and fully mixing, then with the photoreactor sealing, feed high-purity argon 30min to exclude the oxygen in the photochemical reactor, after deoxygenation finishes, continue to stir, and adopt 420nm LED light source to irradiate 8h after stopped reaction.Reaction product is mainly deuterated 2-vinylnaphthalene, and isolated yield is 82% (isolated yield is separated by column chromatography, and rotary evaporation obtains the deuterated 2-vinylnaphthalene product, and the mass calculation that weighs the 2-vinylnaphthalene product then obtains).
[0131] Fig.13 Gas chromatography (GC) detection chart of the photocatalytic selective transfer of deuterated 2-acetylenonaphthalene to prepare deuterated 2-vinylnaphthalene using deuterated water as the deuterium source on carbon nitride-based nickel single-atom photocatalytic material.
[0132] Fig.14 Mass spectrometry (MS) detection diagram of the photocatalytic selective transfer of deuterated 2-acetylenonaphthalene to prepare deuterated 2-vinylnaphthalene using deuterated water as the deuterium source on carbon nitride-based nickel single-atom photocatalytic material.
[0133] Fig.15 Deuterated water was used as a deuterium source to selectively transfer deuterated 2-ethynylnaphthalene to deuterated 2-vinylnaphthalene. The separation of the selective deuterated products was recorded on a 400 MHz Bruker Avance NMR spectrometer. 1 H NMR spectrum). 1 H NMR (400MHz, Methanol-d4) δ7.84-7.71 (m, 4H), 7.65 (dd, J=8.6, 1.8Hz, 1H), 7.45-7.40 (m, 2H).
[0134] The above characterizations prove that deuterated 2-vinylnaphthalene was successfully prepared.
[0135] Comparative Application Example 6
[0136] 20 mg of the Ni / CN sample prepared in Comparative Example 1 was added to 10 mL of a mixed solvent of acetonitrile and deuterated water (volume ratio of 7:3), and then 0.1 mmol of 2-ethynylnaphthalene and 0.5 mmol of triethylamine were added and mixed thoroughly, and then the photoreactor was sealed, and high-purity argon was introduced for 30 minutes to remove oxygen in the photochemical reactor. After deoxygenation, stirring was continued, and the reaction was stopped after irradiation with a 420 nm LED light source for 8 hours. The reaction product was mainly deuterated 2-vinylnaphthalene, and the yield of deuterated 2-vinylnaphthalene was 5% as determined by gas chromatography.
[0137] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a carbon nitride-based nickel single-atom material in catalyzing the selective transfer hydrogenation of alkyne compounds to prepare olefin compounds, characterized in that: The carbon nitride-based nickel single-atom material includes carbon nitride and nickel metal loaded in a carbon nitride skeleton in a single-atom-level dispersed form. The carbon nitride-based nickel single-atom material is represented by Ni1-N4 / CN, where Ni1-N4 represents a nickel single atom and its coordination structure, and CN represents carbon nitride; in Ni1-N4 / CN, one nickel atom coordinates with four nitrogen atoms in the carbon nitride skeleton; In Ni1-N4 / CN, the particle size of single nickel atoms is 0.1~0.2 nm; The method for preparing the carbon nitride-based nickel single-atom material comprises taking a compound containing a nickel element and carbon nitride as raw materials, and carrying out hydrothermal deposition under the action of an organic amine to prepare the carbon nitride-based nickel single-atom material.
2. The use according to claim 1, characterized in that In the Ni1-N4 / CN material, the mass ratio of Ni to CN is 1:(67~500).
3. The use according to claim 2, characterized in that: In the Ni1-N4 / CN material, the mass ratio of Ni to CN is 1:(200~300).
4. The use according to any one of claims 1 to 3, characterized in that: The carbon nitride is prepared by sintering a carbon nitride precursor.
5. The use according to claim 4, characterized in that The carbon nitride precursor is selected from small molecules containing both carbon and nitrogen elements; And / or, the sintering temperature is 500-600°C, and the sintering time is 2-16 h; And / or, the heating rate of the sintering is 2-10°C / min.
6. The use according to claim 1, characterized in that The nickel-containing compound is selected from one or more of nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel perchlorate and their respective hydrates; And / or, the mass ratio of the carbon nitride to the compound containing nickel element is (400:1) to (10:1).
7. The use according to claim 1, characterized in that The organic amine is at least one selected from triethanolamine, triethylamine, n-propylamine and N,N-diisopropylethylamine; And / or, the mass ratio of the carbon nitride to the organic amine is (4:1) to (1:2).
8. The use according to claim 4, characterized in that The carbon nitride precursor is selected from one or more of dicyandiamide, melamine, urea and benzoguanamine.
9. The use according to any one of claims 5 to 8, characterized in that: The method for preparing the carbon nitride-based nickel single-atom material comprises the following steps: Step (1): calcining a carbon nitride precursor at 500-600° C. for 2-16 hours to obtain carbon nitride; Step (2): grinding the carbon nitride obtained in step (1) to obtain a powdered solid, dispersing it in an organic solvent, performing ultrasonic treatment, and then continuing liquid phase exfoliation to obtain a dispersed carbon nitride nanosheet suspension; then mixing the suspension with a compound containing nickel and an organic amine, and stirring; Step (3): subjecting the mixed solution obtained in step (2) to hydrothermal deposition to obtain the carbon nitride-based nickel single-atom material.
10. The use according to any one of claims 1 to 3, characterized in that: The carbon nitride-based nickel single-atom material is used in catalyzing the selective transfer hydrogenation of alkyne compounds to prepare deuterated olefin compounds.
Citation Information
Patent Citations
Nickel single-active site graphite-phase carbon nitride-based photocatalytic material as well as preparation method and application thereof
CN109420514A